Recent Ecological, Physiological And Protein Profile Of The Dengue Vector Population In Penang Island, Malaysia - Rahman, G.M. Saifur (2012)
Inadequate knowledge regarding the risk factors and their interaction is the key problem to face dengue threat. An efficient control of its vectors requires a deep understanding of ecological, physiological and molecular components of their population dynamics. In view with this inference, the study was conducted both, in the field and the laboratory to explore the vector population situation and the interrelated factors involve in their survival, fecundity and mortality. A yearlong larval surveillance in 9 residential areas representing from urban, sub-urban and rural habitats in Penang Island indicated abundant vector population (BI = 79.6 and HI = 44.4) including both, Ae. aegypti and Ae. albopictus. The higher numbers of dengue cases were reported from Ae. aegypti dominated areas that comprised a greater proportion (60%) of the vector population in urban areas, moderate to low in suburban areas and absent from rural areas. They showed equal preference and fitness for breeding indoors and outdoors (7-9 gonotrophic cycles). Aedes albopictus is the only vector in rural areas, found equally both indoors and outdoors, dominant in suburban areas and still competing with Ae. aegypti in outdoor habitats in urban areas. It attained a high population in rural areas through increased gonotrophic activity (up to 14 cycles) by indoor habiting individuals together with increased night time biting activity.